2000
DOI: 10.20870/productions-animales.2000.13.4.3784
|View full text |Cite
|
Sign up to set email alerts
|

La sous-alimentation chez les ruminants : ses effets sur la digestion

Abstract: La relation négative entre le niveau d’ingestion et la digestibilité chez les ruminants a été largement décrite. L’examen de la bibliographie montre que cela est dû à une variation du temps de rétention des particules dans le rumen. Cependant, la majorité des expérimentations a été réalisée à des niveaux d’ingestion supérieurs à l’entretien. Aussi, la présente analyse est centrée sur les travaux réalisés à bas niveaux d’ingestion. Dans ces conditions, la réponse de la digestibilité à une baisse du niveau alime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…This, combined with the decrease in DMI, would explain the decreased milk yield for these cows [12]. Evaluation of various studies under field conditions shows that there is an increase in digestibility in response to high temperature that may be explained by reduced DMI [16] [17] and a prolonged retention of feed in the gastrointestinal tract [18].…”
Section: Heat Stress Effectsmentioning
confidence: 99%
“…This, combined with the decrease in DMI, would explain the decreased milk yield for these cows [12]. Evaluation of various studies under field conditions shows that there is an increase in digestibility in response to high temperature that may be explained by reduced DMI [16] [17] and a prolonged retention of feed in the gastrointestinal tract [18].…”
Section: Heat Stress Effectsmentioning
confidence: 99%
“…However, the field conditions under which the present study was carried out did not allow for indepth studies of the mechanisms underlying the observed changes in gut fill and the physiological consequences for the animal. Reviewing a number of controlled experiments, Doreau et al (2000) concluded that the physiological mechanisms that induce the changes at the level of the digestive system still need to be clarified.…”
Section: On CL U S Io Nsmentioning
confidence: 99%
“…Según señalan Tyrrell y Moe (1975), la depresión de la digestibilidad con el incremento del nivel de alimentación se hace claramente patente para las dietas con alto contenido en concentrado, mientras que cuando los forrajes se ofrecen como único alimento los cambios en la eficiencia digestiva con el incremento del nivel de alimentación son más reducidos. De la revisión efectuada por Doreau et al, (2000), en la que se examinan unas 70 publicaciones que estudiaron la variación de la eficiencia digestiva en ovinos y bovinos con el incremento del nivel de alimentación en dietas de diferente contenido en concentrado, se deduce que para dietas con menos del 20% de concentrado, a una variación del nivel de alimentación entre una y dos veces mantenimiento le correspondería una disminución de la digestibilidad de la materia orgánica (%) de 2 a 3 unidades.…”
Section: Determinación De La Digestibilidad In Vivo De Forrajesunclassified